Recognition of Foreign Divorce Decisions in Indonesia: A Comparative Study of the Principles of Lex Loci Celebrationis and Lex Fori (A Study of How Foreign Divorce Decisions Can Be Recognized in Indonesia and the Legal Obstacles) - Wahid, Luvia; Faiz, Muhammad Jamaludin; Al Amruzi, M. Fahmi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
As more and more individuals enter into marriages with foreign nationals, various legal issues arise, especially when a divorce occurs abroad. In Indonesia, divorce decisions made by foreign courts do not take effect immediately. There are provisions that require the decision to be recognized first by the courts in Indonesia through a process called execution. This article discusses the steps for a foreign divorce decree to be recognized in Indonesia by comparing two legal principles, namely lex loci celebrationis  (the law of the place where the marriage took place) and lex fori (the law of the country where the court is located). From the analysis conducted, it appears that Indonesia mostly refers to the lex fori principle, which makes Indonesian law the main reference. However, there are several obstacles faced, such as the lack of legal cooperation between countries, differences in regulations, and conditions that may be difficult to fulfill by foreign judgments. This research recommends that Indonesia establish stricter regulations and strengthen international legal cooperation to provide legal certainty for those who experience cross-border divorce.